Chemical And Microbiological Properties Of Fermented Dragon Fruit Peel Beverages - Fadhila, Putu Tessa; Kusumasari, Findi Citra; Mardiyanto, Mohammad; Kurniawati, Emi; Sasmita, Irene Ratri Andia (Jurnal Ilmiah Inovasi, 2025)
Dragon fruit peel is rich in bioactive compounds such as betacyanin, betasianidin, polyphenols, and dietary fiber, which can potentially provide health benefits and added value to food products. This research aimed to determine the best formulation of fermented dragon fruit peel beverages based on chemical and microbiology characteristics. The fermentation process is a method for increasing the availability of nutrients in food, as well as creating new compounds that are beneficial for human health. Currently, there is a growing demand for fermented products originating from non-dairy sources, so research on fermented beverages from dragon fruit peel could be an interesting and sustainable solution in the functional food and beverage industry. Chemical analysis in the research conducted includes analysis of reducing sugar, total titratable acidity, and pH, while microbiological analysis was in the form of total lactic acid bacteria. The factor used in this research was the concentration of dragon fruit peel (20%, 40%, 60% and 80%). The results showed that the best formulation was 40% sugar concentration based on reducing sugar (2,92±0,023%,) total titratable acidity (0,27±0,015%), pH (3,53±0,025), and total lactic acid bacteria (4.8 x 109 CFU/ml)